2020
DOI: 10.1371/journal.pone.0239138
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of primary rhegmatogenous retinal detachment repair with extensive scleral-depressed vitreous removal and dynamic examination

Abstract: There are multiple surgical approaches to the repair of rhegmatogenous retinal detachment (RRD). Here, we evaluated the outcomes of small-gauge pars plana vitrectomy (PPV), alone or in combination with scleral buckle (SB-PPV), for RRD repair using a standardized technique by 3 vitreoretinal surgeons: "extensive" removal of the vitreous with scleral depression and dynamic examination of the peripheral retina. One hundred eighty seven eyes of 180 consecutive patients treated for primary RRD by three vitreoretina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In phakic eyes, an increased risk of incomplete vitreous removal and intraoperative breaks with PPV may mediate decreased reattachment rates, even if done in combination with SB [17,55,56]. In the subgroup of pseudophakic eyes, there is a lower risk of incomplete vitreous removal, which was consistent with the observed lack of significant difference between comparators for both primary and final reattachment rates [57,58]. Of note, the use of sectoral and/or encircling buckles was inconsistent among studies with some studies not outlining specific details regarding the procedure performed.…”
Section: Table 3 (Continued)supporting
confidence: 72%
“…In phakic eyes, an increased risk of incomplete vitreous removal and intraoperative breaks with PPV may mediate decreased reattachment rates, even if done in combination with SB [17,55,56]. In the subgroup of pseudophakic eyes, there is a lower risk of incomplete vitreous removal, which was consistent with the observed lack of significant difference between comparators for both primary and final reattachment rates [57,58]. Of note, the use of sectoral and/or encircling buckles was inconsistent among studies with some studies not outlining specific details regarding the procedure performed.…”
Section: Table 3 (Continued)supporting
confidence: 72%
“…VAs of counting fingers, hand motions, and light perception were assigned logMAR values of 2.0, 3.0, and 3.3, respectively. 13 After the distribution of continuous data graphically (histogram and boxplots) was verified and a Shapiro-Wilk normality test was performed, appropriate descriptive terms and statistical tests were used. Categorical variables were assessed using the Pearson chi-square test with Yates continuity correction when applicable.…”
Section: Discussionmentioning
confidence: 99%
“…VAs of counting fingers, hand motions, and light perception were assigned logMAR values of 2.0, 3.0, and 3.3, respectively. 13…”
Section: Methodsmentioning
confidence: 99%
“…Several variables including extent of retinal detachment, previous intraocular surgery, high myopia, and preoperative best-corrected visual acuity have been associated with worse functional outcomes after surgical correction of RRD [ 7 , 8 ]. Macular detachment has also been identified as a major negative prognostic indicator for visual recovery after RRD correction, and standard practice utilizes macular inclusion as a measurement for determining surgical urgency [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise amount of tolerable delay in fovea-involving RRD remains unclear and controversial. While previous studies have concluded functional damage following a macular detachment event is permanent, others have shown that poorer visual outcomes are associated with longer durations of preoperative macular detachment [ 8 10 ]. Mechanistically, studies in animal and cell models have demonstrated that photoreceptor cell death is immediately induced, as early as 12 h after the RD event, and peaks after 2 or 3 days, however, the photoreceptor degeneration processes are complex and are currently not fully understood [ 11 – 14 ].…”
Section: Introductionmentioning
confidence: 99%